Challenging frontiers: Gourmet gastronomy in popular neighborhoods of Buenos Aires - González-Bracco, Mercedes (2024)
The objective of this article is to research the meanings given to gourmet gastronomy in two popular neighborhoods of Buenos Aires, as part of a broader study on processes of commodification and de-stigmatization in urban community tourism projects. The methodology is based on ethnography that includes participant observation and interviews with owners and managers of the gastronomic spaces, visitors, and government officials involved in the promotion of these spaces. The analysis is complemented by the study of press materials and social network publications in order to observe broader implications. In conclusion, although the urban community tourism projects in the neighborhoods studied have developed unevenly, the gastronomic attractions stand out in both proposals. The findings do not offer definitive conclusions on the following issues: 1) the correlation between the growth of these new ventures and 2) the real threats to the revaluation of the spaces where they are located due to the multiplicity of actors involved, the processes of varying duration associated with the socio-spatial imaginaries attributed to popular neighborhoods, and the dynamics of urban cultural consumption.